2018
DOI: 10.7754/clin.lab.2017.170816
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Serum Thiol Levels and Thiol/Disulfide Homeostasis with Head Trauma in Children

Abstract: Analysis of serum thiol levels and SH/SS homeostasis might be useful in order to determine the head trauma in pediatric patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 0 publications
0
13
0
1
Order By: Relevance
“…72 fIGURE 1. miRNA expression in the most common cardiovascular diseases (CVDs). 56,[58][59][60][61][62][63][64][65][66] Moreover, numerous studies demonstrated that the activity of NF-κB has important implications on the he- in CVDs. From a molecular point of view, in the activation of TLR4 intervenes the myeloid differentiation factor 81 (MyD88), which is responsible of the connection between Toll/Interleukin-1 (Toll/IL-1) receptor (TIR) and TLR4.…”
Section: Mirnas and Acute Myocardial Infarctionmentioning
confidence: 99%
See 1 more Smart Citation
“…72 fIGURE 1. miRNA expression in the most common cardiovascular diseases (CVDs). 56,[58][59][60][61][62][63][64][65][66] Moreover, numerous studies demonstrated that the activity of NF-κB has important implications on the he- in CVDs. From a molecular point of view, in the activation of TLR4 intervenes the myeloid differentiation factor 81 (MyD88), which is responsible of the connection between Toll/Interleukin-1 (Toll/IL-1) receptor (TIR) and TLR4.…”
Section: Mirnas and Acute Myocardial Infarctionmentioning
confidence: 99%
“…shows the most important changes in miRNA expression in the most common cardiovascular diseases 56,[58][59][60][61][62][63][64][65][66]. Nf-κB, INfLAmmATION, AND ATHEROSCLEROSISAnother important factor involved in the molecular mechanisms that lay at the basis of cardiovascular dis-eases is represented by nuclear factor kappa B (NF-κB) 15.…”
mentioning
confidence: 99%
“…Following after withdrawn brain CTs, the risk of malignancies occurence associated with ionizing radiation in children increases (17). Exposure to ionizing radiation during CT scans has been shown to increase the risk of brain tumor and leukemia per mGy in children by 0.016 and 0.033, respectively (18). Also in another study which was made, radiation exposure after CT extractions in children creates a higher risk of cancer compared to adults (19).…”
Section: Discussionmentioning
confidence: 98%
“…In recent years, some biomarkers (lymphocyte, hemoglobin, hemotocrit, S100B, lactate, thiol) have been thought to assist in determining the prognosis in childhood head traumas and studies have been conducted associated with this [9,10,11]. In our study, the relationship between age, gender, trauma etiology, presence of symptoms at the time of admission, GCS, brain CT ndings and blood WBC levels at the time of application in cases of head trauma between the ages of 0-18, who were admitted to the emergency department in Turkey's Kars province were examined.…”
Section: Introductionmentioning
confidence: 99%